Why is energy access not enough for choosing clean cooking fuels? Sustainable development goals and beyond - Zhanna Kapsalyamova; Ranjeeta Mishra; Aiymgul Kerimray; Kamalbek Karymshakov; Dina Azhgaliyeva (Asian Development Bank Institute (ADBI), 2021)
The transition to sustainable energy requires an assessment of drivers of the use of clean and dirty fuels for cooking. Literature highlights the importance of access to modern fuel for switching from dirty fuels. Though access to cleaner fuels such as electricity promotes clean fuel use, it does not necessarily lead to a complete transition to the use of modern fuels. Households continue using traditional fuels in addition to modern fuels. The main objective of this paper is to explain the choice of dirty cooking fuels even when access to electricity is provided. We use nationally representative household survey data to study the household energy use decisions in three middle-income countries, India, Kazakhstan, and the Kyrgyz Republic. The study discusses the role of access to natural gas, free fuel, convenience or multi-use of fuels determined by the heating system installed, built-in environment, and other socioeconomic factors in household fuel choice for cooking. The results show that access to natural gas increases the likelihood of opting for natural gas, while the availability of free fuel in rural areas and the coal-based heating system promote the use of solid fuels.
Keywords: Q41; Q31; Q48; 330; cooking fuel; fuel choices; energy access; multiple fuel use; Sustainable Development Goals (SDGs)